“MADNESS AS RESISTANCE: SUBVERTING PATRIARCHAL CONTROL IN HAN KANG'S THE VEGETARIAN" - Muhammad Fauzi Razak; Nur Sapta Riskiawati; Sofyan Sukwara Akfan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article examines the concept of madness as a form of resistance in Han Kang's novel The Vegetarian, which deeply depicts a woman's psychological and bodily rebellion against the shackles of a patriarchal and conformist Korean society. The main character, Yeong-hye, exhibits behavior labeled as "madness" after she decides to stop eating meat—a decision that later develops into a rejection of language, social expectations, and even her own body. Drawing on Michel Foucault's theory of madness as a social construction and R.D. Laing's anti-psychiatry perspective, this study argues that Yeong-hye's descent into what is considered madness is not simply a mental disorder, but a conscious form of resistance embodied through the body. Her rejection of familial and societal norms represents an attempt to reclaim agency in a world that often oppresses women's subjectivity. Through a close reading of the narrative, this article reveals how The Vegetarian critiques mechanisms of control, discipline, and normalization within domestic and institutional structures. Ultimately, Yeong-hye's madness emerges as a counter-narrative that shakes the rational order and challenges dominant ideologies about gender, conformity, and sanity.